2022
DOI: 10.3201/eid2805.220166
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in First Dose COVID-19 Vaccination Coverage among Children 5–11 Years of Age, United States

Abstract: A lthough more common among adults, severe coronavirus disease (COVID-19) and hospitalization can occur in children. Among >8,300 hospitalized children 5-11 years of age, 1/3 required intensive care (1,2). Children can transmit severe acute respiratory syndrome coronavirus 2 to others, highlighting the need for pediatric COVID-19 vaccinations. On November 2, 2021, the US Centers for Disease Control and Prevention (CDC) recommended the use of the Pfizer-BioNTech COVID-19 vaccine (Pfizer Inc., https://www.pfizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 5 publications
4
37
0
Order By: Relevance
“…The higher COVID-19 vaccination coverage among Asian non-Hispanic children is consistent with other studies and with what has been found for influenza vaccination. 6,20…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The higher COVID-19 vaccination coverage among Asian non-Hispanic children is consistent with other studies and with what has been found for influenza vaccination. 6,20…”
Section: Discussionmentioning
confidence: 99%
“…The NIS-CCM survey weights adjust for non-response and households without cellular telephones and were calibrated to match counts of children with one or more doses of COVID-19 vaccine by sex within each U.S. Department of Health and Human Services (HHS) region for children ages 5–11 years as of mid-month, using data reported to CDC by jurisdictions. 6 T-tests for proportions were used to test for statistically significant differences with p <0.05. The NCHS reliability criteria for proportions was implemented and proportions not meeting the criteria were suppressed from the tables.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations